PENGARUH EMPLOYEE ENGAGEMENT TERHADAP KINERJA KARYAWAN PADA PT. SINAR KENCANA MULTI LESTARI - Cintani Cintani; Noviansyah Noviansyah (KOLEGIAL, 2020)
This study aims to determine the Effect of Employee Engagement on Employee Performance At PT. Sinar Kencana Multi. Data analysis technique used is simple linear regression. Based on the results of analysis by using hypothesis test (t-test) obtained t-count (11.143)> t-table (2.03951) then Ho rejected and Ha accepted. This means that there is a significant influence employee engagement on Employee Performance at PT. Sinar Kencana Multi Lestari. The calculated coefficient of determination (R2) obtained for 0800. This indicates 80%. Employee Performance at PT. Sinar Kencana Multi Lestari is influenced by employee engagement while the remaining 20% ​​is influenced by other variables mentioned in this research such as individual and organizational factors (Mangkunegara, 2005: 14).